Civil society organizations, the Good Friday Agreement, and the Northern Ireland peace process - Byrne, Sean (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2023)
A qualitative methodology was used to interview 120 participants from 2010 and 29 participants from 2020 who shared their experiences and perceptions about the Good Friday Agreement (GFA) and their peacebuilding work. Longitudinal findings reveal that the participants were critical of the Agreement and the disconnect between politicians and the grassroots as well as recognizing that the Agreement has brought about relative peace in Northern Ireland. While the participants attest to the relative success of the GFA, they also note several criticisms including sectarian politics, new paramilitaries, Brexit, legacy of the past, continuing divisions in Northern Ireland, and the disconnect between politicians and local community peacebuilders. The participants’ criticisms are significant as they attest that while the social peace at the grassroots level is moving forward the political peace is not as evidenced by the recent Unionist backlash against Brexit.
Keywords: gospodarska pomoč; organizacije civilne družbe; Severna Irska; Velikonočni sporazum; vzpostavitev miru